Initiating The ASEAN Arbitration Board as a Forum for Settlement of Investment Legal Disputes in The Framework of Integration of The ASEAN Economic Community (AEC) Region - Marulak Pardede (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
The impact of liberalization and globalization of the world economy is that all countries in the ASEAN region, have become an area of a borderless economic community (AEC). This has triggered an increase in the foreign investment business and its legal disputes, which of course need legal certainty for dispute resolution. The parties must resolve it through general courts (litigation), or alternative dispute resolution out of court or arbitration (non-litigation). Therefore, it becomes a legal issue: what are the legal aspects of resolving legal disputes between the Indonesian government and foreign investors; and what efforts should be made to facilitate the settlement of investment law disputes, within the framework of regional integration of the ASEAN economic community? This study aims to analyze investment dispute resolution and the idea of establishing an MEA arbitration body as a forum for resolving investment legal disputes between business actors. This study uses a normative juridical method, which is based on library research to obtain secondary data, sourced from primary, secondary, and tertiary legal materials. The specifications of the analytical descriptive research describe the establishment of the MEA arbitration body and the potential positive impacts. The data analysis method used is juridical qualitative. The results of the study indicate that the development of investment business legal dispute resolution in the MEA area requires the AEC Arbitration Board as a forum for resolving investment disputes between business actors, mainly due to differences in legal systems between countries.